Peer-editing practice in the writing classrooms: Benefits and drawbacks - Ann Rosnida Mohd Deni, *; Zainor Izat Zainal, (2009)
Small scale studies have shown that peer-editing is beneficial to students as it increases their awareness of the complex process of writing improves their knowledge of and skills in writing and helps them become more autonomous in learning. Teachers too may benefit from peer-editing as this practice discloses invaluable information on students’ writing weaknesses and strengths; and teachers’ teaching effectiveness. This is a small scale study conducted on fifteen first-year degree students majoring in Tourism to view the usefulness of peer-editing practice in enhancing their writing skills....1 PEER-EDITING PRACTICE IN THE WRITING CLASSROOM: BENEFITS AND DRAWBACKS Ann Rosnida Md. Deni Zainor Izat Zainal Small scale studies have shown that peer-editing is beneficial to students as it increases their awareness of the complex process of writing improves their knowledge of and skills in writing and helps them become more autonomous in learning. Teachers too may benefit from peer-editing as this practice discloses invaluable information on students’ writing weaknesses and strengths; and teachers’ teaching effectiveness. This is a small scale study conducted on fifteen first-year degree students majoring in Tourism to view the usefulness of peer-editing practice in enhancing their writing skills. Retrospective notes were taken to record students’ receptiveness and reaction towards peer editing practice; students’ writing samples and peer-editing questionnaires were analysed to view students’ revisions and comments; and an open-ended questionnaire was distributed to identify students’ perceptions of peer-editing practice in the writing classroom. Analysis of data gathered revealed that peer-editing practice benefitted both the teacher and most of her students as it exposed important information that could improve her teaching of writing and her students’ writing practices.